Development of nanocomposite scaffolds based on TiO2 doped in grafted chitosan/hydroxyapatite by freeze drying method and evaluation of biocompatibility - Abd-Khorsand, Saber; Saber-Samandari, Samaneh; Saber-Samandari, Saeed (Elsevier Science Bv, 2017)
Porous three-dimensional scaffolds with potential for application as cancellous bone graft substitutes were prepared using the freeze-drying technique. Hydroxyapatite with different weight ratio was embedded in the network of poly(acrylic acid) grafted chitosan accompanied by using TiO2 as an auxiliary component to fabricate porous nanocomposite bone scaffolds. Fourier transform infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction analysis and mechanical tests were carried out to characterize the prepared scaffolds. These scaffolds showed well controlled and interconnected porous structures. The pore size and porosity of the scaffolds could be effectively modulated by selecting appropriate amounts of hydroxyapatite. The results obtained from mechanical properties measurements indicated that the scaffolds could basically retain their strength in their dry state and have adequate mechanical properties close to those of cancellous bone. The swelling behavior of the scaffolds was also examined in both water and phosphate buffer saline solution. The cytotoxicity of the scaffold was determined by MTT assays on human fibroblast gum (HuGu) cells for 24, 48 and 72 h. In conclusion, this investigation demonstrates that the fabricated nanocomposite scaffolds are suitable for bone tissue engineering. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Bone tissue engineering; Scaffold; Titanium dioxide; Hydroxyapatite; Chitosan